OP89 Risk of miscarriage associated with maternal and paternal smoking. (2nd September 2014) - Meaney, S; Corcoran, P; Lutomski, JE; Spillane, N; O'Donoghue, K
Abstract : Background: Maternal smoking has been associated with increased risk of miscarriage. However little is known about the influence of paternal smoking. The study aimed to examine maternal and paternal smoking as risk factors for miscarriage. Methods: A cohort study was conducted in a large, tertiary hospital (8500 deliveries per annum) in the Republic of Ireland in 2012. Women randomly selected at their first booking visit (10–14 weeks) were asked to complete a detailed lifestyle questionnaire including maternal and paternal smoking and the mother's exposure to partner's smoke. All participants were followed up at 20 weeks gestation to determine pregnancy outcome. Results: Of the 417 participants, the prevalence of maternal and paternal smoking was 26.3% and 30.7%, respectively, and 13.4% of mothers were exposed to their partner's smoke. One in three (n = 134, 32.1%) had a confirmed miscarriage at follow-up. Miscarriage was not associated with maternal smoking (30.6% for non-smokers versus 32.4% for smokers; P = 0.737) or paternal smoking (31.2% for non-smokers versus 32.8% for smokers; P = 0.763). A higher proportion of women exposed to their partner's smoke experienced miscarriage (44.2% vs. 29.9%; Odds ratio=1.86, 95% CI=1.03–3.38; P = 0.038). The association remained even after adjustment for the mother's own smoking (Adjusted odds ratio=2.22, 95% CI=1.12–4.40; P = 0.022). Conclusion: Our findings suggest an association between mother's exposure to partner's smoke and miscarriage. That risk of miscarriage could be influenced by passive smoking but not active smoking is biologically implausible. However, a mother's exposure to her partner's smoke may be a proxy for other risk factors that warrant further investigation.